A diverse saurischian (theropod–sauropod) dominated footprint assemblage from the Lower Cretaceous Jiaguan Formation in the Sichuan Basin, southwestern China: A new ornithischian ichnotaxon, pterosaur tracks and an unusual sauropod walking pattern. (May 2016) - Xing, Lida; Lockley, Martin G.; Marty, Daniel; Klein, Hendrik; Yang, Geng; Zhang, Jianping; Peng, Guangzhao; Ye, Yong; Persons, W. Scott; Yin, Xianya; Xu, Ting
Abstract: A sample of fallen blocks of fluvial sandstone from the Lower Cretaceous Jiaguan Formation of Sichuan Province yielded an assemblage of dinosaur and pterosaur tracks preserved as natural impressions and casts. Collectively the assemblage reveals 132 tracks representing at least 30 trackways of tridactyl and didactyl theropods, sauropods, ornithopods and pterosaurs. Ichnotaxonomically, the trackways of small tridactyl theropods (pes lengths 7–18 cm) are indeterminable, whereas the trackway of a small didactyl dromaeosaur (pes length up to 7.5 cm) is tentatively assigned to cf. Velociraptorichnus . The sauropod trackways are assigned to cf. Brontopodus based on the medium to nearly wide-gauge pattern. Other characteristics are the U-shaped manus and strong heteropody. One sauropod trackway shows a peculiar pattern with a lack of left manus imprints, and an unusual position and rotation of right manus imprints. Different scenarios and explanations for this phenomenon are discussed. Ornithopod trackways are the most abundant in the sample and characterized by pes imprints of a small biped that are assigned here to the new ichnospecies Caririchnium liucixini . It is characterized by an unusual broad shape and weak mesaxony. Bivariate analysis of different Caririchnium ichnospecies reveals increasing mesaxony toward the larger forms, a trend that is the reverse of typical theropod ichnotaxa, where large imprints have weak mesaxony. Three isolated, small pterosaur tracks (two manus, one pes) are visible on a single surface. They show strong similarities to the widespread ichnogenus Pteraichnus . This is the ninth report of tetrapod tracks from the Jiaguan Formation in recent years and represents one of the most diverse assemblages recorded to date. It is also rare evidence of typical didactyl dromaeosaur tracks and the co-occurrence of sauropod and ornithopod tracks in a fluvial depositional environment representing arid climate conditions.